2009
DOI: 10.1080/09537100802458969
|View full text |Cite
|
Sign up to set email alerts
|

Increased mean platelet volume in patients with slow coronary flow

Abstract: Mean platelet volume (MPV) is an indicator of platelet activation, a central process in the pathophysiology of coronary heart disease (CAD). The importance of slow coronary flow (SCF) phenomenon results from its association with angina pectoris, acute myocardial infarction, hypertension and sudden cardiac death. The aim of this study is to evaluate the values of MPV in patients with SCF. MPV was measured in 84 consecutive patients with SCF and 88 patients with CAD and 84 control subjects. The association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 37 publications
3
30
1
Order By: Relevance
“…On these grounds, MPV could be accepted as a parameter of platelet activity and has become a prognostic factor in coronary heart disease [25]. Previous studies have demonstrated a close relationship between MPV and AMI [8], unstable coronary syndromes [26], slow coronary ow [27] and coronary artery ectasia development [28]. High MPV values were found to be associated with unsuccessful reperfusion a er both primary percutaneous coronary intervention and brinolytic therapy [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…On these grounds, MPV could be accepted as a parameter of platelet activity and has become a prognostic factor in coronary heart disease [25]. Previous studies have demonstrated a close relationship between MPV and AMI [8], unstable coronary syndromes [26], slow coronary ow [27] and coronary artery ectasia development [28]. High MPV values were found to be associated with unsuccessful reperfusion a er both primary percutaneous coronary intervention and brinolytic therapy [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is detected that PTX-3 is also produced at atherosclerotic plaque. Demonstration of correlated increase of PTX-3 secreted from neutrophils and platelet aggregation in acute coronary syndrome (20) may be one reason of increased platelet aggregation shown in patients with SCF (21). Level of PTX-3 was shown to increase in acute atherothrombosis in CAD, and was accepted as a predictor of mortality (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients' cardiac, hepatic and respiratory system characteristics were also not investigated in the study. Pathologies relating to these systems had the ability to cause changes in MPV values [19][20][21][22] . Also in that study, it was not clear how the diagnosis of synovitis was made.…”
Section: Discussionmentioning
confidence: 99%